The effect of innovation and consumer related factors on consumer resistance to innovation - Mazhar Abbas; Muhammad Shahid Nawaz; Jamil Ahmad; Muhammad Ashraf (Cogent Business & Management, 2017)
Implementations of technological innovations have been playing key roles for firms to grow and survive in the long run particularly in a dynamic and complex market and unstable economic conditions. The success of any innovation in the market which highly depends on consumers could be one of the potential factors behind the failure of the innovation. Research on innovation resistance is still in infancy and effort to describe the resistance as well as understanding the consumers' resistance to innovation still requires in-depth investigations including the context of resistance to innovation. As a response to this problem, this study examines the consumers' resistance to innovation through measuring the resistance to smartphones. This study is grounded by the resistance to innovation and appraisal theories. In the research framework, this study includes consumers' characteristics (motivation, self-efficacy, emotion (negative), and attitude toward existing product) and innovation characteristics (relative advantage, perceived risk, complexity, social influence, and price). A cross sectional, survey data were gathered from 307 university students of four public universities in Pakistan via self-administered survey questionnaires. They were statistically tested using PLS (SEM) path modeling. The results demonstrate the concept of consumers' resistance to innovation in the context of Pakistan.
Keywords: 650